Self-Instruction in Islamic Religious Education Learning: Improving Critical Thinking and Student Motivation: Self-Instruction dalam Pembelajaran PAI: Meningkatkan Berpikir Kritis dan Motivasi Belajar Siswa - Firmansyah; Ali, Mukti; Rosad, Ade; Fauzi, Muhamad; Husni, Miftahul (Halaqa: Islamic Education Journal, 2025)
This study aims to explore the effectiveness of the Self-Instruction technique in improving students' critical thinking skills and learning motivation in learning Islamic Religious Education (PAI). With a library research approach using the Systematic Literature Review (SLR) method, the study analysed various academic sources, including relevant journals, textbooks and research reports. The results showed that the Self-Instruction technique contributes to building students' thinking independence, enhancing analytical understanding of Islamic concepts, and encouraging deep reflection on the application of religious values in daily life. This technique allows students to be more active in analysing religious arguments, developing rational arguments, and strengthening systematic thinking skills in understanding Islamic teachings. In addition, the application of this technique is proven to increase students' learning motivation and confidence in exploring their religious understanding more critically and reflectively. The findings of this study have important implications in the development of more innovative and self-reflection-based learning strategies in PAI learning, and can be the basis for PAI teachers in applying more effective methods in building learning motivation, as well as analytical and argumentative mindsets in students. Highlights: Critical Thinking – Strengthens independent analysis and reasoning in Islamic studies. Learning Motivation – Boosts confidence and reflective exploration of religious concepts. Innovative Teaching – Supports self-reflective and analytical learning in PAI. Keywords: Critical Thinking, Learning Motivation, Pai Learning, Self-Instruction